The Influence of Hard skills, Organizational learning and Soft skills on Teacher innovation capability during digital era - Asbari, Masduki (PROFESOR : Professional Education Studies and Operations Research, 2024)
This study aims to measure the influence of organizational learning on the improvement of hard skills, soft skills and teacher innovation capability in Indonesia.Hard skills and soft skills as mediated variables. Data collection was carried out by simple random sampling via electronic to a population of teachers in Banten . The returned and valid questionnaire results were 800 samples. Data processing using SEM method with SmartPLS 3.0 software. The results of this study are organizational learning has a positive and significant effect on teacher innovation capability, both directly and through mediating hard skills and soft skills. This novel research is proposing a model to build teacher innovation capability among teachers through organizational learning with hard skills and soft skills as mediation. This research can open the way to improve teacher readiness in facing the era of education 4.0.